الحوافز المادية ودورها في تحقيق التوافق المهني - معروف, سميحة; صوالح, حليمة (University of Eloued جامعة الوادي, 2023)
الملخـــــــــــص: هدفت دراستنا إلى معرفة الحوافز المادية والتي تمثلت في المكافآت والترقيات والخدمات الإجتماعية ودورها في تحقيق التوافق المهني، وقد إعتمدنا في دراستنا على المنهج الوصفي لإعتباره ملأم لموضوعنا،كما إستندنا على الإستبيان كأداة لدراسة، حيث إشتملت عينة الدراسة على 50فرداً من عمال المؤسسة العمومية للصحة الجوارية بجَامْعَةٌ، ولاية المغير، الجزائر، وقد تمت بطريقة عشوائية، وفي النهاية قمنا بوضع الملاحق وقائمة المصادر والمراجع حيث توصلنا إلى النتائج التالية: - أن المؤسسة تعتمد على الحوافز المادية في تحسين أداء العاملين. - إثبات فرضيات البحث التي تقول بأن للحوافز المادية دور في تحقيق التوافق المهني، فهنا يجب على المؤسسة بأن تسعة إلى تقديم تحفيزات إلى عماله التحقق أهدافها وأهداف موضفيها. ونضيف كذلك الكلمات المفتاحية الخاصة بدراستنا فنذكر منها: الحوافز المادية والتوافق المهني والمؤسسة. Summary: Our study aimed to know the material incentives, which were rewards, promotions and social services and their role in achieving professional compatibility, and the main objective of this study is to know the extent of the role of material incentives in achieving professional compatibility, while the sub-objectives are to reveal the role of rewards in achieving professional compatibility within the organization As well as knowing the role of promotions in achieving professional compatibility within the institution, and knowing the role of social services in achieving compatibility - Do material incentives have a role in the professional compatibility of the worker in the institution? Questions derive from it, as follows: Does the rewards have a role in achieving the professional compatibility of the employee in the institution? - Do promotions have a role in achieving the professional compatibility of the employee in the institution? - Do social services have a role in achieving a role for the worker in the institution? As for the hypotheses of the study, it was represented in the main hypothesis, the material incentives have a role in achieving the professional compatibility of the worker in the institution, and the sub-hypotheses were included under it, namely, rewards have a role in achieving the professional compatibility of the worker in the institution, promotions have a role in achieving professional compatibility when working in the institution, promotions have a role in Achieving professional compatibility among the worker in the institution. Social services have a role in achieving professional compatibility among the worker in the institution In our study, we relied on the descriptive approach because it is appropriate for our subject, and we also relied on a questionnaire as a tool for the study, and that frequencies, percentages, the arithmetic mean, and the standard deviation, while the program used is spss, where the study sample consisted of 50 individuals from the workers of the Public Institution for Surrounding Health at the University of El Moghir Province, Algeria. Done in a way randomly, and in the end we put the appendices and a list of sources and references, where we reached the following results: - The institution relies on financial incentives to improve the performance of employees. Proof of the research hypotheses that say that material incentives have a role in achieving professional compatibility. - The organization provides bonuses to employees. _ Social services contribute significantly to achieving professional compatibility. We also add the keywords of our study, including: (material incentives, professional compatibility, and the institution)
دراسة ميدانية في المؤسسة العمومية لصحة الجوارية _جَامْعةُ
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: الحوافز المادية، des incitations matérielles, material incentives; التوافق المهني، compatibilité professionnelle, professional compatibility